2017
DOI: 10.1371/journal.pone.0177691
|View full text |Cite
|
Sign up to set email alerts
|

The cryptic plasmid is more important for Chlamydia muridarum to colonize the mouse gastrointestinal tract than to infect the genital tract

Abstract: Chlamydia has been detected in the gastrointestinal tracts of both animals and humans. However, the mechanism by which Chlamydia colonizes the gut remains unclear. Chlamydia muridarum is known to spread from the genital to the gastrointestinal tracts hematogenously. The C. muridarum plasmid is a key pathogenic determinant in the mouse upper genital tract although plasmid-deficient C. muridarum is still able to colonize the upper genital tract. We now report that plasmid-deficient C. muridarum exhibits signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 62 publications
(125 reference statements)
2
43
0
1
Order By: Relevance
“…It is worth noting that deficiency in pGP3 reduced C. muridarum survival in the stomach by more than 100-fold, while the reduction in survival in the vagina was only ϳ8-fold. This discrepancy is consistent with previous observations that loss-of-function mutations in genes carried in the C. muridarum plasmid or genome caused a more dramatic phenotype in the GI tract than in the genital tract (28)(29)(30)53). The GI tract antimicrobial machineries, such as gastric acid and digestive hydrolases, are more robust than those in the genital tract.…”
Section: Fig 10supporting
confidence: 91%
See 3 more Smart Citations
“…It is worth noting that deficiency in pGP3 reduced C. muridarum survival in the stomach by more than 100-fold, while the reduction in survival in the vagina was only ϳ8-fold. This discrepancy is consistent with previous observations that loss-of-function mutations in genes carried in the C. muridarum plasmid or genome caused a more dramatic phenotype in the GI tract than in the genital tract (28)(29)(30)53). The GI tract antimicrobial machineries, such as gastric acid and digestive hydrolases, are more robust than those in the genital tract.…”
Section: Fig 10supporting
confidence: 91%
“…Recent studies have shown that vaginal C. muridarum can not only ascend to the oviduct but also spread to the GI tract (26) via a hematogenous route (27) to establish long-lasting colonization in the GI tract. Interestingly, this genital-to-GI-tract spreading seems to correlate with C. muridarum induction of hydrosalpinx in the genital tract (28)(29)(30). These observations have led to the proposal of a two-hit model partially explaining C. muridarum pathogenicity in the upper genital tract (7).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…C. trachomatis is naturally transmitted among humans sexually, while C. muridarum may be naturally transmitted among mice via the oral-fecal route (instead of sexually). This is because the C. muridarum plasmid or plasmid-encoded proteins or some chromosomal proteins have been shown to be more important for C. muridarum to colonize the GI tract than to infect the genital tract (47,48). In addition, the C. muridarum genome still maintains three copies of a full-length cytotoxin gene with significant homology to genes for large clostridial cytotoxins (49).…”
Section: Discussionmentioning
confidence: 99%